Comparison of Total Flavonoid, Phenolic Levels, and Antioxidant Activity between Robusta and Arabica Coffee - Ngibad, Khoirul; Yusmiati, Siti Nur Husnul; Merlina, Diana Mey; Rini, Yenny Puspa; Valenata, Valenata; Jannah, Elok Faiqotul (KOVALEN: Jurnal Riset Kimia, 2023)
Coffee contains a lot of phenolic compounds, especially chlorogenic acid, therefore many studies have examined the potential of coffee as an antioxidant. Antioxidants can inactivate oxidation reactions and prevent the formation of free radicals. This research aimed to determine the total phenolic and flavonoid content of the ethanol extract of robusta coffee (Coffea canephora) and the ethanol extract of arabica coffee (Coffea arabica), as well as determine the % inhibition value of Arabica coffee ethanol extract and Robusta coffee ethanol extract and their combination as antioxidants in vitro. Robusta and Arabica coffee powders were soaked in ethanol solvent, respectively, and the filtrate was concentrated using a rotary evaporator. The extract’s flavonoid and total phenolic content were measured by UV-Vis spectrophotometry. An antioxidant activity test was carried out using the DPPH method. The phenolic content of the ethanol extract of robusta coffee powder and the ethanol extract of arabica coffee powder were 7.98 and 9.16 mg QE/g, respectively. The total flavonoid content of the ethanol extract of robusta coffee powder and the ethanol extract of arabica coffee powder were 11.5 and 14.2 mg GAE/g, respectively. The highest % inhibition values of the ethanol extract of arabica coffee powder and the ethanol extract of robusta coffee and their combination as antioxidants in vitro were 71.1, 85.1, and 86.4%.